Germ cell tumors: Insights from the Drosophila ovary and the mouse testis - Salz, Helen K. (Mol Reprod Dev, 2017)
Ovarian and testicular germ cell tumors of young adults are thought to arise from defects in germ cell development, but the molecular mechanisms underlying malignant transformation are poorly understood. In this review, we focus on the biology of germ cell tumor formation in the Drosophila ovary and the mouse testis, for which the evidence supports common underlying mechanisms such as blocking initiation into the differentiation pathway, impaired lineage progression, and sexual identity instability. We then discuss how these concepts inform our understanding of the disease in humans.